(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Angioperm flora of Manikgonj Sadar Upazila has been partially inventoried. A total of 207 species under 72 families and 174 genera has been recorded. Among those, the division Magnoliopsida represents 147 species belonging to 56 families and 127 genera, and the division Liliopsida represents 60 species belonging to 16 families and 47 genera. DOI: http://dx.doi.org/10.3329/jasbs.v39i2.17851 J. Asiat. Soc. Bangladesh, Sci. 39(2): 147-166, December 2013